Condicionamento osmótico e qualidade de sementes de milho doce durante o armazenamento - Basso, Denise Puntel [UNESP] (2014)
The sweet corn seeds possess characteristics that contribute to decrease the physiological quality of its seeds, such as high levels of sugar over starch, high sensitivity to damage during imbibition. In addition, the seeds have also susceptibility to fungi, which favored the loss of viability, vigor and reduced longevity during storage. In this context, the use of priming may increase the uniformity and speed of germination and therefore improve seed quality. However, it is not known whether the osmoprimed seeds could be stored under special conditions for maintaining the quality obtained by the treatment. This study aims to determine the effect of priming of sweet corn seeds during storage. The seeds were treated with solutions of polyethylene glycol (PEG 6000) and evaluated every two months over a period of six months. The experimental design was completely randomized, factorial 2 x 4 (Conditioned and unconditioned and 4 days of storage) with 4 replications. The seeds were dried and subsequently stored in plastic bags, under laboratory conditions and in cold chamber. We evaluated the water content, germination, first count of germination, electrical conductivity, accelerated aging, germination in sand, speed of seedling emergence and seedling length, seedling dry matter. The results were submitted to analysis of variance (ANOVA), and the averages were compared by the Tukey test at 5 % of probability. It was concluded that primed showed a better quality but it is lost during storage.